2016
DOI: 10.1530/eje-15-1065
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Metabolic and inflammatory pathways on the pathogenesis of type 2 diabetes

Abstract: Obesity is the main risk factor for type 2 diabetes (T2D). Studies performed over the last 20 years have identified inflammation as the most important link between these two diseases. During the development of obesity, there is activation of subclinical inflammatory activity in tissues involved in metabolism and energy homeostasis. Intracellular serine/threonine kinases activated in response to inflammatory factors can catalyse the inhibitory phosphorylation of key proteins of the insulin-signalling pathway, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 167 publications
0
38
0
4
Order By: Relevance
“…Chronic insulin resistance continuously pressures β cells to produce insulin. This may lead to endoplasmic reticulum stress and low‐grade inflammation, with resultant negative effects on β cells. Given a diabetes‐prone genetic background, such effects could underlie a successive demise of β cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic insulin resistance continuously pressures β cells to produce insulin. This may lead to endoplasmic reticulum stress and low‐grade inflammation, with resultant negative effects on β cells. Given a diabetes‐prone genetic background, such effects could underlie a successive demise of β cells.…”
Section: Discussionmentioning
confidence: 99%
“…When T2DM, hyperinsulinemia and insulin-resistance occur, chronic inflammation increases and affects disease development and related complications [41]. IL-17, a proinflammatory cytokine, plays a prominent role in neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have shown that obese individuals present an increase in adipose tissue macrophages and other immune cell infiltration [1]. These cells are key drivers of inflammation via overproduction of inflammatory cytokines, including interleukin (IL)-1β, tumor necrosis factor-α (TNF-α) and IL-6, which are strongly associated with the progression of the obese phenotype and metabolic traits of type 2 DM [36,37]. In addition, the abnormal infiltration of immune cells in adipose tissue has deleterious long-term consequences on the biology of this tissue, as adipocytes are major targets of the pro-inflammatory effects of cytokines released by immune cells [38].…”
Section: Cytokines and Adipokines In Obesity And Type 2 Dmmentioning
confidence: 99%